Causes of Demotivation in Sanskrit Education: A Narrative Inquiry - Adhikari, Rishiram (Journal of Research and Analysis, 2026)
Sanskrit is one of the oldest languages and is also known as a main source of eastern knowledge. However, in the present time the motivating factors of Sanskrit study is being weakened in Nepal. In this context, the study analyzes the causes of the demotivating of youth in Sanskrit studies in Nepal. The purpose of this study has examined why students are demotivated to study Sanskrit in higher education and what the main factors are responsible for not pursuing Sanskrit studies. The study has followed a qualitative research design and analyzed the narratives of the participants about Sanskrit studies and causes of not to demotivate to continue higher education. In depth study has used to collect data from the field. Three individuals were purposely selected for this study as participants and asked questions about the demotivating factors of continuing Sanskrit education. The conclusion is based on the primary data; however, secondary sources of data were also used in the review section. The findings have indicated that students are demotivated to pursue Sanskrit education due to several reasons: limited job opportunities, outdated teaching methods, the perceived impracticality of the curriculum, and a lack of social respect for the discipline. These factors significantly discourage young students to continue the Sanskrit education at higher levels.